Rapid Deployment Aortic Valve Replacement with the Perceval S and Intuity Elite - Liakopoulos, Oliver J.; Gerfer, Stephen; Rahmanian, Parwis; Eghbalzadeh, Kaveh; Djordjevic, Ilija; Schlachtenberger, Georg; Zeriouh, Mohamed; Mader, Navid; Choi, Yeong-Hoon; Wahlers, Thorsten (The Thoracic and Cardiovascular Surgeon, 2020)
Background Rapid deployment aortic valve replacement (RDAVR) has emerged as an alternative to conventional aortic valve replacement. This single-center study retrospectively analyzed clinical outcomes and hemodynamic performance of the Perceval S (LivaNova) and Intuity Elite (Edwards LifeSciences) rapid deployment valves (RDVs) in a propensity score matched patient cohort.Methods A total of 372 consecutive patients with symptomatic aortic valve stenosis underwent RDAVR between 2012 and 2018 at our institution. The Intuity Elite (INT group) and Perceval S (PER group) were implanted in 251 and 121 patients, respectively. After 1:1 propensity score matching for relevant preoperative comorbidities, 107 patient pairs were compared with respect to relevant perioperative data including hemodynamic parameter, postoperative pacemaker implantation, and 30-day all-cause mortality.Results Propensity score matching resulted in balanced characteristics between groups. Cardiopulmonary bypass and aortic cross-clamp time did not differ between groups, but more patients in the INT group received coronary artery bypass grafting compared with the PER group (56 vs. 42%; p = 0.055). Thirty-day mortality (4.7 vs. 2.2%) and need for permanent pacemaker implantation (7 versus 4.4%) were comparable between the INT and PER groups for isolated AVR and also for combined procedures, respectively. Cerebrovascular events showed comparable low rates for both RDVs (INT group [1.9%] vs. PER group [2.8%]). Indexed effective orifice area was higher in the INT group (0.90 vs. 0.82 cm2/m2) and coupled to a lower peak (17 ± 7 vs. 22 ± 8) and mean (10 ± 5 vs. 12 ± 4) pressure gradients compared with the PER group.Conclusions Our propensity score analysis in AVR patients showed good hemodynamic characteristics with comparable 30-day mortality rate and complications rates for both investigated RDVs.
Keywords: aortic valve and root; heart valve surgery; cardiac; minimally invasive surgery